PERBEDAAN KADAR PROLYLCARBOXYPEPTIDASE DI PASIEN SINDROM KORONER AKUT DENGAN PASIEN ANGINA STABIL (The Difference of Prolylcarboxypeptidase Level in Acute Coronary Syndrom and Stable Angina Patient) - Maenaka Smaratungga; Rita C; Indrati AR; Martha JW (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Coronary arterial disease (CAD) is the main cause of mortality across many countries throughout the world. Formation ofatherosclerosis plaque is the early cause for cardiovascular dysfunction in CAD. Detecting of atherosclerosis plaque instability is veryimportant to predict the risk of acute coronary syndrome (ACS). Various biomarkers have been studied to find the good marker fordetecting atherosclerosis and its instability, but until now there is no biomarker meet the requirements to be used in routine clinicaltests. Prolylcarboxypeptidase (PRCP) is the alternative parameter in the detection of atherosclerosis, assessing the degree of its plaqueand instability in CAD patients. The benefits of PRCP level test in serum, compared to angiography that is currently used in the detectionof atherosclerosis plaque is that this test is non-invasive, provides quantitative level information, able to estimate the instability of theplaque and the fact that it is a laboratorial test that can be performed in hospitals with less advance facilities. The aim of this study isto know the different PRCP level between ACS and stable angina patients by determination. This study was held in the period betweenMarch–May 2014, in Rumah Sakit dr. Hasan Sadikin Bandung. The subjects were selected on the basis of consecutive sampling onpatients that are presented in the Emergency Departement and Cardiovascular Clinic. From 88 patients consisted of 44 patients withACS and 44 patients with stable angina, were tested for PRCP level in the serum using the ELISA sandwich method. This study wascarried out by observational design with cross sectional method. The statistical analysis uses the Saphiro Wilk data normality test,Mann Whitney test and Kruskal Wallis test. There was no characteristic difference between the two groups. This research identifiedsignificant difference of PRCP level between the ACS group and stable angina (P=0.005). Prolylcarboxy peptidase level in the ACS group(156,3×102 pg/mL) is higher compared to the stable angina (143.8×102pg/mL). PRCP level test hopefully can be recommended asone of the laboratorycal parameter in measuring the degree and instability of atherosclerosis plaque, in the absence of angiography orintravascular ultrasonography test facility.